2014
DOI: 10.1021/es501115c
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Using On-Farm Flood Flow Capture To Recharge Groundwater and Mitigate Flood Risks Along the Kings River, CA

Abstract: The agriculturally productive San Joaquin Valley faces two severe hydrologic issues: persistent groundwater overdraft and flooding risks. Capturing flood flows for groundwater recharge could help address both of these issues, yet flood flow frequency, duration, and magnitude vary greatly as upstream reservoir releases are affected by snowpack, precipitation type, reservoir volume, and flood risks. This variability makes dedicated, engineered recharge approaches expensive. Our work evaluates leveraging private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 7 publications
4
75
0
Order By: Relevance
“…Therefore, a large amount of nitrogen and chloride could have leached into the shallow groundwater with the flood waters. In their studies on surface and aquifer water quality in the Sanjiang Plain, Cao et al [17] and Bachand et al [31] found that Cl − and NO3 − concentrations and EC all increased during floods on farmland due to the infiltration of surface application of fertilizers and pesticides. Cao et al's study [17] showed several wells in the region with suspiciously high NO3 − concentrations (up to 153.29 mg/L).…”
Section: Effect Of the 2013 Summer Flood On Water Qualitymentioning
confidence: 99%
“…Therefore, a large amount of nitrogen and chloride could have leached into the shallow groundwater with the flood waters. In their studies on surface and aquifer water quality in the Sanjiang Plain, Cao et al [17] and Bachand et al [31] found that Cl − and NO3 − concentrations and EC all increased during floods on farmland due to the infiltration of surface application of fertilizers and pesticides. Cao et al's study [17] showed several wells in the region with suspiciously high NO3 − concentrations (up to 153.29 mg/L).…”
Section: Effect Of the 2013 Summer Flood On Water Qualitymentioning
confidence: 99%
“…In the same way that Apple assembled existing microprocessor, battery and display technologies and developed the iPhone, a number of researchers, including Helen Dahlke (UC Davis), Phil Bachand (Bachand & Associates) and others, are combining underutilized resources -winter flood flows, water conveyance infrastructure and offseason farmland -together to create something new (Bachand et al 2013;Bachand et al 2016;Harter and Dahlke 2014;O'Geen et al 2015).…”
Section: The Role Of Innovationmentioning
confidence: 99%
“…In addition, recent work by Bachand et al [67] also demonstrates the potential of alfalfa fields and vineyards to be used for additional groundwater recharge, e.g., using flood waters. Alfalfa and vineyards were selected for the analysis here also because they are in high demand, are suited to the local climate, and require little or no nitrogen fertilizer; as a leguminous N-fixer, alfalfa can be expected to produce relatively low amounts of N leaching, while allowing for significant groundwater recharge through intentional over-irrigation.…”
Section: Beneficial Agricultural Management Practices In Buffer Zonesmentioning
confidence: 99%
“…Recharge basin installation and operating costs is on the order of $20,000/hectare annualized [85]. However, supplemental surface water used for recharge in the buffers may help prevent or alleviate flood damage; flood damage from the Kings and San Joaquin Rivers is estimated at $740 million since 1983 [67,86]. Benefits from avoided damage costs elsewhere are yet to be estimated; however, the calculations used here account for flood damage avoidance costs.…”
Section: Estimated Cost Of Conversionmentioning
confidence: 99%
See 1 more Smart Citation